Large-area photonic bound state in the continuum for ultraviolet and deep-blue emission for organic, inorganic, and perovskite scintillators - Kowal, Dominik (2023)
Optimizing the emission properties of materials in ultraviolet and deep blue (UV-DB) is interesting in the development of new scintillator devices for the detection of X-ray, ray, and radiation particles, as those materials can be strong candidates for high light yield and fast scintillators. While their intrinsic material properties are already well studied, photonic enhancement generated through optical confinement could significantly improve their emission characteristics; however, one needs to overcome the problem of relatively low refractive indices contrast resulting in poor confinement of UV-DB light. This motivates the search for resonator structures built from readily accessible materials that can boast strong confinement in this spectral regime. Here, we present such a structure, leveraging bound states in the continuum (BICs) to realize large-area confinement of UV-DB light with ultrahigh quality factors up to Q 107. These ultrahigh Q -factors, in turn, result in strong enhancements in light emission via the Purcell effect. We demonstrate the operation of such a design by simulating the mode shape, Q -factor, and emission behavior in organic, hybrid perovskite, and III-V scintillating materials. By tailoring the structure geometry, it can be robustly tuned to match the emission characteristics of chosen materials. We start with considering ideal infinite structure supporting perfect BIC; we extend our model on finite-sized structures, and we discuss the limitations associated with the self-absorption and thickness of the structure. Our findings pave the way to cost-effective and efficient designs for scintillators in the UV-DB regime.